2007
DOI: 10.1242/dev.02858
|View full text |Cite
|
Sign up to set email alerts
|

A discrete period of FGF-induced Erk1/2 signalling is required for vertebrate neural specification

Abstract: Neural tissue formation is induced by growth factors that activate networks of signal transduction cascades that ultimately lead to the expression of early neural genes, including transcription factors of the SoxB family. Here,we report that fibroblast growth factor (FGF)-induced Erk1/2 (Mapk3 and Mapk1,respectively) mitogen-activated protein kinase (MAPK), but not phosphatidylinositol 3′-OH kinase (PI3K, Pik3r1), signalling is required for neural specification in mouse embryonic stem (ES) cells and in the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
257
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(291 citation statements)
references
References 40 publications
32
257
1
1
Order By: Relevance
“…Cells were transferred from 2i to N2B27, and BI was applied for 25 h. We analysed cells on days 2 and 3, when Oct4‐negative/Sox1‐positive neural precursors begin to emerge 17, 33, 70. No significant effects were observed on day 2.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were transferred from 2i to N2B27, and BI was applied for 25 h. We analysed cells on days 2 and 3, when Oct4‐negative/Sox1‐positive neural precursors begin to emerge 17, 33, 70. No significant effects were observed on day 2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, EGFR is a receptor for several ligands, including Egf1 and TGFa, that acts on a plethora of signaling pathways including mitogen-activated protein kinase (MAPK) and Rac pathways, and therefore plays a crucial role in promoting proliferation, migration, differentiation, and survival. 105 Another protein that appears to play a role in neurogenic processes after HI is the fibroblast growth factor receptor 1 (Fgfr1), which promotes progenitor proliferation 106 and neuronal fate commitment in proliferating cells. 107,108 A recent study showed that ablation of the Fgfr1 gene from GFAP-expressing cells in mice leads to attenuated cell proliferation in the SVZ and decreased cortical pyramidal neuron production after HI.…”
Section: Molecular and Cellular Processes In The Neurovascular Niche mentioning
confidence: 99%
“…ES cells respond to autocrine FGF signaling to convert to Sox1 þ NPCs [28,30]. We hypothesize that it is this step at which exogenous GAGs have their effect [25].…”
Section: Gags Modulate the Fgf-dependent Step That Initiates Sox1 Expmentioning
confidence: 99%
“…We then used the Ext1 À/À ES cell line to show that, although in the absence of cell surface HS ES cells fail to achieve successful neuroectodermal differentiation, this can be compensated by soluble heparin [25]. In this study, we have interrogated the specific role of HS in early signaling events during exit from self renewal into primitive ectoderm and subsequently neuroectoderm [26][27][28]. We have used the 46C ES cell line to investigate the effect of glycosaminoglycan (GAG) addition to HS-competent cells, demonstrating that GAG can be a positive or negative regulator of differentiation, dependent on size and sulfation pattern of the chains.…”
Section: Introductionmentioning
confidence: 99%